Proses Akomodasi Komunikasi Petugas Kesehatan dengan Pasien di Rumah Sakit Bhayangkara TK. III Padang - Putra, Nofri Andeska; Arif, Ernita; ., Azwar (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This study explores the communication accommodation process between healthcare providers and patients in improving health services at Bhayangkara Hospital Level III Padang. The research problem focuses on the complexity of communication in police hospitals with unique hierarchical rank structures, where data shows low referral rates of West Sumatra Police personnel (25.8%) and variations in patient satisfaction regarding healthcare provider communication aspects. This study aims to analyze the communication accommodation process, identify strategies implemented by healthcare providers, and analyze factors influencing the process. The research uses qualitative methods with a case study approach and constructivist paradigm, involving 15 informants from hospital management, healthcare providers, and patients selected through purposive sampling. Data collection was conducted through in-depth interviews, non-participant observation, and documentation study, then analyzed using the interactive model of Miles, Huberman, and Saldana with NVivo 12 assistance. Research findings identify four stages of iterative-adaptive communication accommodation process (initial assessment, communication adaptation, understanding verification, and further modification), six accommodation strategies (interpretability, convergence, divergence, emotional expression, discourse management, and interpersonal control), and four factors influencing the process (structural-institutional, individual, situational, and policy-program factors). The research produces a new theoretical model called "Adaptive-Hierarchical Communication Accommodation" that explains the phenomenon of "adaptation duality" where healthcare providers perform dual adaptation to individual patient characteristics and their hierarchical positions. Research recommendations include adopting the four-stage model as an integrated communication operational standard, developing adaptive-hierarchical communication training programs and implementing objective triage systems with strengthening the "Professional First, Rank Second" principle to improve healthcare service quality in police hospitals.